HUBUNGAN KOMPENSASI DAN PENILAIAN KINERJA DENGAN KETERIKATAN PEGAWAI (Studi kasus pada PT. Haleyora Power) - Purwa Ragata; Radjab Tampubolon; Jan Horas V. Purba (MAGMA : JURNAL MAGISTER MANAJEMEN, 2019)
The purpose of this study is to know whether there is a relationship between compensation and performance appraisal with employee attachment. The population of this research is the employees of PT Haleyora Power technical services with the number of 230 employees. Sampling technique using Slovin after calculated obtained the number of samples as 147 employees. The research instrument is kusioner. The data collected is then processed using correlation analysis techniques with the help of SPSS software. The method used is survey and data analysis techniques using statistical test of correlation and simple linear regression and multiple linear regression. The hypothesis testing performed at a significant level of 0.05. Result of research yield three conclusion that is: First there is significant positive correlation between compensation with employee attachment with regression equation Ŷ = 22.369 + 0,917X1 and relationship that happened between compensation with employee attachment including category "very strong" because that value ry.1 = 0,992 is between 0,800 - 1,00. Second, there is a significant positive correlation between performance appraisal and employee attachment with regression equation Ŷ = 19.136 + 0.907X2. and the relationship between performance appraisal and employee attachment is "strong" because the value of ry.2 = 0.988 is between 0,800-1.00. Third, there is a significant positive correlation between compensation and performance appraisal together with employee attachment with regression equation Ŷ = 20,986 + 0,652X1 + 0,265X2 and correlation coefficient ry1.2 equal to 0,993. Based on these matters, it can be concluded that employee engagement can be improved through compensation and performance appraisal.